Green synthesis of orange emissive carbon dots for the detection of Ag+ and their application via solid-phase sensing and security ink. (29th October 2021) - Bai, Haiyan; Chen, Weixing; Yang, Jin; Cao, Yixin; Yu, Jiajia; Zhao, Huaqi; Zhou, Hongwei; Jin, Xilang
Abstract: Fluorescent carbon dots (CDs) have attracted considerable interest due to their superior optical properties and facile preparation. In this work, O-phenylenediamine and melamine were used as precursors for the one-step hydrothermal synthesis of novel orange emissive CDs (O-CDs) in an aqueous solution. The fluorescence intensity (580 nm) of the O-CDs exhibited a good linear relationship with Ag + in the range of 0.0–50.0 μ M with the detection limit of 0.289 μ M. Moreover, the O-CDs were successfully used to determine Ag + in biological samples (Hela cells) because of their low cytotoxicity, and good biocompatibility. Besides, the O-CDs-doped solid-phase detection materials (test paper and hydrogel) were employed to monitor Ag + qualitatively and quantitatively, indicated that the O-CDs had a great capacity for the detection of Ag + in biological and environmental areas. Based on their extraordinary fluorescence property, the O-CDs could also be used as security ink. Overall, based on their excellent fluorescent performance, the CDs in this study have significant potential for practical application toward solid-phase sensing and security ink.